2022
DOI: 10.1007/s12035-022-02817-3
|View full text |Cite
|
Sign up to set email alerts
|

Serpin Signatures in Prion and Alzheimer’s Diseases

Abstract: Serpins represent the most broadly distributed superfamily of proteases inhibitors. They contribute to a variety of physiological functions and any alteration of the serpin-protease equilibrium can lead to severe consequences. SERPINA3 dysregulation has been associated with Alzheimer’s disease (AD) and prion diseases. In this study, we investigated the differential expression of serpin superfamily members in neurodegenerative diseases. SERPIN expression was analyzed in human frontal cortex samples from cases o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 106 publications
(130 reference statements)
2
24
0
Order By: Relevance
“…This upregulation was later confirmed in human frontal cortex specimens from patients affected with different types of prion diseases, both at the protein and transcript levels . A SERPINA3/SerpinA3n (its functional murine orthologue) role in prion propagation was further corroborated by our recent observation of SerpinA3n-dependent prion accumulation changes in scrapie-infected cells . Therefore, these findings make SERPINA3 an attractive target for non-PrP-targeted anti-prion drug strategies …”
Section: Introductionsupporting
confidence: 59%
See 2 more Smart Citations
“…This upregulation was later confirmed in human frontal cortex specimens from patients affected with different types of prion diseases, both at the protein and transcript levels . A SERPINA3/SerpinA3n (its functional murine orthologue) role in prion propagation was further corroborated by our recent observation of SerpinA3n-dependent prion accumulation changes in scrapie-infected cells . Therefore, these findings make SERPINA3 an attractive target for non-PrP-targeted anti-prion drug strategies …”
Section: Introductionsupporting
confidence: 59%
“…It is noteworthy that SERPINA3 overexpression appears to be correlated also with Alzheimer’s disease, ,, multiple system atrophy, and amyotrophic lateral sclerosis pathology; therefore, our therapeutic strategy could be potentially applied to treat other prion-like neurodegenerative disorders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overexpression of SERPINA3 in the brain of AD patients correlates with tau hyperphosphorylation and senile plaque deposition ( 42 ). Recently, Vanni et al reported that SERPINA3 expression in the brain is increased during aging and highly upregulated in patients with neurodegenerative disorders such as prion disease and Alzheimer's disease ( 43 , 44 ). Cognitive decline is one of the most important signs preceding the onset of Alzheimer's disease.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from various strategies that target Prp C or PrP Sc , a novel non-PrP targeted drug strategy emerged as an effective approach to treat prion disease [ 298 ]. Upregulation of SerpinA3/SerpinA3n has been associated with NDDs, including prion disease [ 299 ] as a serine protease inhibitor, it retards the protease activity responsible for clearing prion protein aggregates. With this idea, a small molecule serpin inhibitor (ARN1468) has been designed which effectively reduced prion load in scrapie’s infected ScN2a RML and ScN2a 22 L cell lines.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%